Synthesis of a non-stationary system of automatic control of flight of an airplane with decrease in glisade - Краснопольський, А. О. (Proceedings of National Aviation University (archive), 2021)
The method of synthesis of the structure of a non-stationary automatic control system is proposed, which allows a large gain without disturbance of stability. As a result of the development of such a system, an adaptive system was created in the form of an algorithm and a structural scheme that can be used in the program of the onboard computing complex. For example, an aircraft of civil aircraft. The adaptive automatic control system, which makes automatic adjustment of the gain, proceeds from the requirements of the specified stability of the transition process